Java : - Savitch, Walter (Pearson Prentice Hall, 2005)
In a conversational style, best-selling author Walter Savitch teaches programmers problem solving and programming techniques with Java. Introduces object-oriented programming and important computer science concepts such as testing and debugging techniques, program style, inheritance, and exception handling. Includes thorough coverage of the Swing libraries and event-driven programming. Provides a concise, accessible introduction to Java that covers key language features. Covers objects thoroughly and early, with an emphasis on applications over applets. A useful reference for programmers who want to brush up on their Java skills.